Pengembangan Angket Respon Mahasiswa Terhadap Penggunaan Laboratorium Virtual Selama Pandemi Covid-19 - Sri Rejeki Dwi Astuti; Rizki Nor Amelia; Anggi Ristiyana Puspita Sari; Karlinda (FKIP Universitas Palangka Raya, 2023)
In the covid-19 pandemic, teaching and learning activities was conducted online. Thus, we need an application that can support distance learning, including the practicum process in the laboratory. Virtual laboratory is considered to be the main solution in replacing the learning process in the laboratory. However, by utilizing virtual laboratory in the learning process did not necessarily hone students' practical skills. Therefore, we aimed to develop and to explore the validity and reliability of Student responses questionnaire towards the virtual laboratories during the Covid-19 pandemic. This research was research and development adopting the 4D model. This research involved 2 evaluation experts and 63 students of chemistry department of UNY selected based on purposive sampling technique. The research instruments were content validation sheets for experts and developed questionnaires for construct validation. The data were analyzed with descriptive qualitative technique to describe product development process data, Aikens' V analysis to analyze content validity data, Exploratory Factor Analysis to analyze construct validity data, and Cronbach Alpha analysis to analyze questionnaire reliability using SPSS 20. The results revealed that the student response questionnaire towards virtual laboratory has been successfully developed using the 4D model consisting of 11 statements. All statements in the questionnaire were proved valid based on construct validity and reliable. From the findings, the student response questionnaire is ready to be used for further research related to student responses to learning media.